Testing for weak D Antigen: Spectrum and its applied role in rhesus-negative transfusions in Andaman and Nicobar Islands - Rupinder Kaur Brar; P S Shaiji; Sahil Sehgal (Tzu-Chi Medical Journal, 2020)
Objectives: Rhesus (Rh) blood group with variable expression of D antigen is one of the complex systems in immunohematology. Weak D antigen is a phenotype where the D antigen is weakly expressed on red blood cells, and this antigen cannot be detected by routine methods. This study was conducted to determine the frequency of Rh D negativity and weak D antigen among healthy blood donors and to review the clinical significance of weak D antigen pertaining to Rh D-negative transfusions. Materials and Methods: This cross-sectional prospective study was conducted in G. B Pant Hospital from January 2016 to June 2017 in which all the blood donors from Port Blair and adjacent islands of Andaman and Nicobar were grouped for Rh D antigen and those who tested negative for the D antigen were further tested for weak D antigen by incubating for 30 min and subsequent addition of anti-human globulin sera. Results: Out of 6415 donors, 6085 (94.86%) were Rh D positive and 330 (05.14%) were Rh D negative. Among the Rh D-negative donors, 05 (01.51%) were positive for weak D antigen. The frequency of Rh D negativity was 25.76% in a blood group, 25.15% in B, 07.88% in AB and 41.21% in O blood group phenotype. Conclusion: Although the frequency of weak D antigen is low (01.51%), the strong immunogenicity of Rh D antigen discernates the need for appropriate testing for weak D antigen. This is of particular concern in Rh D-negative pregnant females as it can produce alloimmunization if accidentally given weak D antigen positive blood.